Increased osteoblast adhesion on titanium‐coated hydroxylapatite that forms CaTiO3 - Webster, Thomas J.; Ergun, Celaletdin; Doremus, Robert H.; Lanford, William A. (Wiley, 2003)
AbstractCaTiO3 is a strong candidate to form at the interface between hydroxylapatite (HA) and titanium implants during many coating procedures. However, few studies have compared the cytocompatibility properties of CaTiO3 to HA pertinent for bone–cell function. For this reason, the objective of the present in vitro study was to determine the ability of bone‐forming cells (osteoblasts) to adhere on titanium coated with HA that resulted in the formation of CaTiO3. To accomplish the formation of CaTiO3, titanium was coated on HA discs and annealed either under air or a N2+H2 environment. Materials were characterized by X‐ray diffraction (XRD), Rutherford backscattering spectroscopy (RBS), and atomic force microscopy (AFM). These characterization techniques demonstrated the formation of a nanometer rough CaTiO3 layer as a consequence of interactions between HA and titanium during coating conditions. Results from cytocompatibility tests revealed increased osteoblast adhesion on materials that contained CaTiO3 compared to both pure HA and uncoated titanium. The greatest osteoblast adhesion was observed on titanium‐coated HA annealed under air conditions. Because adhesion is a crucial prerequisite to subsequent functions of osteoblasts (such as the deposition of calcium containing mineral), the present in vitro results imply that orthopedic coatings that form CaTiO3 could increase osseointegration with juxtaposed bone needed for increased implant efficacy. © 2003 Wiley Periodicals, Inc. J Biomed Mater Res 67A: 975–980, 2003
Keywords: Titanium; Osteoblasts; Oxides; Calcium Compounds; Microscopy, Atomic Force; Durapatite; Coated Materials, Biocompatible; X-Ray Diffraction; Osseointegration; Bone Substitutes; Cell Adhesion; Animals; Humans